Plan social media como herramienta para mejorar la notoriedad de la identidad corporativa de Diario El nacional de Machala - Chavarría Reyes, Leonela Joselyn (Machala, 2019)
This research project is about the proposal of a model of social media plan for the newspaper "El Nacional" in the city of Machala, where it is proposed to improve the notoriety of the corporate identity of the media. Through interviews with experts, the tools and requirements for the correct creation and performance of the plan were identified since publishing content on social networks of a company or organization implies a series of analysis about the target audience to which our content is directed, also take care of the identity we project to the followers. For a complete analysis regarding the social networks of the newspaper, the observation technique was also applied, where it was allowed to corroborate the deficit of reach in terms of followers and interaction. In the same way, through surveys of readers of the newspaper, some opinions were identified regarding the corporate identity that “El Nacional” projects, as well as preferences regarding the type of publications that readers prefer in social networks. “El Nacional” newspaper currently has a Facebook and Instagram account, where as a result of the investigation the problem on which the project is based was evidenced, which is the absence of interaction in official social networks and the low visibility of its corporate identity in the web. Thanks to the research techniques and methods, some key aspects were known for the creation of the social media plan, where it was also necessary to visit the media and talk with the director of the same to learn about the corporate identity of the newspaper. With the presence of all the data obtained from the investigation, we proceeded to develop the proposal of a model of social media plan for Facebook and Instagram, which include objectives at a certain time, actions to be taken to increase the interaction and number of followers, rules and guidelines for the use and style of social networks and their advantages. The final product of our project, that is, the social media plan was presented to the manager and journalist of the media, who took into consideration the actions and recommendations recorded through the investigation. Social networks, thanks to web 2.0, offer a space where you can interact with other users by exchanging images, videos, messaging; that is to say, users become content generators, facilitating the communication process in the hands of technology. When mentioning about the management, management and consumption of social networks, most professionals in the field of communication and marketing talked about the correct planning with which they should handle these platforms. Currently one of the most debated issues worldwide, is whether traditional media with technological advancement will disappear, a reality that the owners and managers of these media should pay attention to avoid being affected by the cyber current. This project also determined the importance of creating a Social Media Plan for the correct dissemination of content on social networks, in the same way it is essential for a media to keep updated digitally, since the way to consume the information It changes as technology advances and new generations demand it.
El presente proyecto de investigación trata sobre la propuesta de un modelo de plan social media para diario “El Nacional” de la ciudad de Machala, donde se plantea mejorar la notoriedad de la identidad corporativa del medio de comunicación. Por medio de entrevistas a expertos se identificó las herramientas y requerimientos para la correcta creación y desempeño del plan ya que el publicar contenido en redes sociales de una empresa u organización implica una serie de análisis acerca del público objetivo al que va dirigido nuestro contenido, también cuidar de la identidad que proyectamos a los seguidores. Para un completo análisis en cuanto a las redes sociales del diario, también se aplicó la técnica de la observación, donde se permitió corroborar el déficit de alcance en cuanto a seguidores e interacción. De la misma forma por medio de encuestas a lectores del diario se identificó algunas opiniones en cuanto a la identidad corporativa que proyecta “El Nacional”, también las preferencias en cuanto al tipo de publicaciones que prefieren los lectores en redes sociales. Diario “El Nacional” actualmente tiene cuenta en Facebook e Instagram, donde como resultado de la investigación se evidenció el problema del cual se basa la el proyecto, que es la ausencia de interacción en las redes sociales oficiales y la poca notoriedad de su identidad corporativa en la web. Gracias a las técnicas y métodos de investigación se conoció algunos aspectos claves para la creación del plan social media, donde también fue necesario visitar el medio de comunicación y dialogar con el director del mismo para conocer sobre la identidad corporativa del diario. Con la presencia de todos los datos obtenidos de la investigación, se procedió a desarrollar la propuesta de un modelo de plan social media para Facebook e Instagram, donde incluyen objetivos a un tiempo determinado, acciones a tomar para aumentar la interacción y cantidad de seguidores, normas y pautas de uso y estilo de las redes sociales y ventajas de las mismas. El producto final de nuestro proyecto, es decir el plan social media se presentó ante el directivo y periodista del medio de comunicación, quién tomó en consideración las acciones y recomendaciones registradas por medio de la investigación. Las redes sociales, gracias a la web 2.0 ofrecen un espacio donde se permite interactuar con demás usuarios intercambiando imágenes, vídeos, mensajería; es decir, los usuarios se convierten en generadores de contenido, facilitando el proceso comunicacional de la mano de la tecnología. Al momento de mencionar sobre la gestión, manejo y consumo de las redes sociales, la mayoría de profesionales en la rama de comunicación y marketing hablaron sobre la correcta planificación con la que deben manejar estas plataformas. Actualmente uno de los temas de mayor debate a nivel mundial, es sobre si los medios de comunicación tradicionales con el avance tecnológico desaparecerán, realidad que los dueños y directivos de estos medios deben prestar atención para evitar verse afectados por la corriente cibernética. En este proyecto también se determinó la importancia de la creación de un Plan Social Media para la correcta difusión de contenidos en redes sociales, de la misma forma lo esencial que es para un medio de comunicación mantenerse actualizado digitalmente, ya que la forma consumir la información cambia conforme la tecnología avanza y las nuevas generaciones lo exigen.
Keywords: SOCIAL MEDIA; IDENTIDAD CORPORATIVA; RED SOCIAL; COMUNICACION DIGITAL